2019
DOI: 10.32098/mltj.01.2014.08
|View full text |Cite
|
Sign up to set email alerts
|

Learning about PRP using cell-based models

Abstract: Studies using in vitro cell models enable evaluation of the effects of different PRP products under very controlled and standardized conditions. Therefore the results of such studies build the basis for understanding the variable results of clinical studies on the use of PRPs. The main lessons learned through the use of in vitro cell models are that many different PRP products exist and researchers have to report on component variation within each product. These different products may have distinctive effects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
10
0
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 53 publications
(88 reference statements)
0
10
0
1
Order By: Relevance
“…To date there are several commercially available PRP systems 9,15,55 , which differ among them in either the centrifugation method, platelet concentration, release rate of growth factors 9,56,57 , white 58,59 and red blood cell concentration and/or activation 60 . Differences among PRP commercial presentations have not been clarified, regarding the optimal concentration of growth factors delivery and their effects on tendon regeneration.…”
Section: Limitations Of Use Of Prpmentioning
confidence: 99%
“…To date there are several commercially available PRP systems 9,15,55 , which differ among them in either the centrifugation method, platelet concentration, release rate of growth factors 9,56,57 , white 58,59 and red blood cell concentration and/or activation 60 . Differences among PRP commercial presentations have not been clarified, regarding the optimal concentration of growth factors delivery and their effects on tendon regeneration.…”
Section: Limitations Of Use Of Prpmentioning
confidence: 99%
“…In vitro studies showed that PRP, in particular leukocyte-rich plasma (L-PRP), is able to suppress inflammatory mediator concentration and gene expression in synovium and cartilage tissue, 9 and this could explain the pain improvement and promising results in some clinical series. Although there have been many clinical studies on the anti-inflammatory effects of corticosteroids and hyaluronic acid (HA) injections for knee OA, 10 clinical studies using PRP are limited.…”
Section: Introductionmentioning
confidence: 99%
“…Tissue wound repair is a complex process in which a variety of cellular functions such as chemotaxis, angiogenesis, cell pro liferation, extracellular matrix formation and the «cleansing» macrophage coexist, sequentially and covertly [5,6]. These func tions form a complex in which three relatively distinct phases are classically distinguished: inflammation, proliferation and remod eling 3, 4, 5, 6, 7.…”
mentioning
confidence: 99%
“…and the type of tissue (tendon, muscle, bone, etc.). PAP efficacy for the cells reparation process activation was demonstrated experimentally and confirmed in few clinical stud ies but researches used different PAP preparations so results often are not comparable [6]. Also platelet quantification and the growth factor content definition must be defined in order to understand molecular mechanisms behind PRP regenerative strength.…”
mentioning
confidence: 99%
See 1 more Smart Citation